Molecular and genetic characteristics of Epstein-Barr virus isolates in adult patients with HIV infection in Nizhny Novgorod region - Mariia I. Popkova; E. N. Filatova; S. V. Minaeva; N. A. Sakharnov; O. V. Utkin (Инфекция и иммунитет)
Introduction. According to foreing studies, the Epstein–Barr virus (EBV) isolates from individuals infected with the human immunodeficiency virus (HIV) are characterized by specific molecular genetic features compared to immunocompetent individuals. In Russia, no studies have yet been conducted to assessing EBV molecular genetic diversity in HIV-patients. The aim of the study is to assess EBV molecular genetic diversity in adult HIV-patients in the Nizhny Novgorod region. Materials and methods. EBV isolates derived from blood leukocytes of 138 HIV-infected patients aged 20–69 years (HIV(+) group) and 68 HIV-uninfected sex- and age-matched (HIV(–) group) individuals were studied. For differential detection of EBV-1/EBV-2, there were used PCR variant with electrophoretic detection of amplification products in agarose gel. Nucleotide sequences of the C-terminal fragment LMP-1 gene were determined by Sanger sequencing. Phylogenetic analysis was performed using MEGA X software. Results. In the typical structure of Nizhny Novgorod region EBV isolates in the adults HIV(–) group, only EBV-1 was detected. In the HIV(+) group detection rate of EBV-1 was 88.2±3.4%, EBV-2 — 5.4±2.3%, EBV-1+EBV-2 — 6.4±2.6% cases. In the EBV strain structure based on the classification by R. Edwards et al. five LMP-1 variants were identified: B95-8, China 1, Med–, NC and Alaskan, among which B95-8 was dominant. However, their frequency rate did not differ between the HIV(+) and HIV(–) groups. In general, in HIV infection, the appearance of recombinant EBV LMP-1 variants, a wider range of deletions, prominent variability in the tandem repeat region with the presence of modified motifs and point amino acid substitutions therein have been noted, and 57 amino acid substitutions have been described that were previously found in the Nizhny Novgorod region EBV isolates was not detected. Conclusion. For the first time in Russia, molecular genetic EBV diversity in adult HIV-patients was carried out. The results obtained build up the basis for a prospective study on a relationship between clinical and laboratory characteristics for EBV+HIV co-infection and genetic heterogeneity of EBV population at the level of virus types, variants and subvariants.